Credit card debt and payment use - Charles Sprenger; Joanna Stavins (Federal Reserve Bank of Boston, 2008)
Approximately half of credit card holders in the United States regularly carry unpaid credit card debt. These so-called revolvers exhibit payment behavior that differs from that of those who repay their entire credit card balance every month. Previous literature has focused on the adoption of debit cards by people who carry credit card balances, but so far there has been no empirical analysis exploring the relationship between revolving behavior and patterns of payment use, such as substitution away from credit cards to other payment methods. Using data collected in the 2005 Survey of Consumer Payment Preferences, we explore the relationship between revolving credit card balances and payment use. We find that credit card revolvers are significantly more likely to use debit and less likely to use credit than convenience users who repay their balances each month. There is no significant difference between these two types of credit card users in their use of check or cash. The two groups differ in their perceptions of payments as well as in their payment behavior: revolvers are significantly less likely to view debit as superior with respect to ease of use and acceptability, but more likely to see debit as superior with respect to control over money and budgeting.
Keywords: D12; D14; E21; 330; Payments; credit card; debit card; consumer credit; Kreditkarte; Verbraucherkredit; Konsumentenverhalten; USA